Answer:
Step-by-step explanation:POOHSHIESTYDATSMYDAWGBUTPOOHYKIMREALLYSHIESTY
Answer:
x=36
Step-by-step explanation:
First rewrite equation then multiply each side by 36. 9x-36=4x+144.
then move the variable 9x-4x+36=144. Next subtract 9x and 4x ...5x=144+36.... 5x=180. Lastly you divide 180÷5 this your answer x=36
Umm no you need to do your own work and do not be asking for answers
Nothing is handed to you ....you need to work HARD to get what you want.
Given equations are;<span>
2a + 3b = -1 ..................equation 1
3a + 5b = -2 ....................equation 2</span>
Now multiply equation 1 with (-3)
The equation will be;
-6a -9b = 3 …………………..equation 3
Now multiply equation 2 with (2)
The equation will be;
6a + 10b = -4 ……………..equation 4
Now add equation 3 and equation 4
-6a – 9b = 3
<span>6a + 10b = -4</span>
<span>------------------------------</span>
0a + b = -1
b = -1
Now put the value of b in equation 1
2a + 3(-1) = -1
2a -3 = -1
2a = -1+3
2a = 2
a=1
Thus the solution is (a,b) = (1,-1)
<span>
</span>